2017
DOI: 10.1111/nep.12795
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and morphologic spectrum of renal involvement in patients with HBV‐associated cryoglobulinaemia

Abstract: Nephrotic syndrome with haematuria and renal insufficiency are the main clinical manifestation; cryoglobulinaemic glomerulonephritis are the main renal lesion in patients with HBV-Associated cryoglobulinaemia; half of patients have poor outcome even with antiviral and immunosuppressive therapy. The results of this study indicate that cryoglobulins should be detected in hepatitis B virus-Associated nephropathy in endemic area.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
31
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(38 citation statements)
references
References 22 publications
6
31
0
Order By: Relevance
“…We observed microtubule structure in only one case on electron microscopy. These findings were consistent with the ultrastructural features of HBV related CryoGn reported in the literature [6,10]. In one previous study including 12 patients of CryoGn associated with HBV infection, only two cases were found microtubule substructure on electron microscopy [6].…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…We observed microtubule structure in only one case on electron microscopy. These findings were consistent with the ultrastructural features of HBV related CryoGn reported in the literature [6,10]. In one previous study including 12 patients of CryoGn associated with HBV infection, only two cases were found microtubule substructure on electron microscopy [6].…”
Section: Discussionsupporting
confidence: 91%
“…This finding was consistent with that of Italian study which reported type II cryoglobulins accounted for 88% in HBV related cryoglobulinemic vasculitis [5]. However, result in another previous Chines study suggested that type III cryoglobulinemia was more frequently seen in HBV related CryoGn [6]. This discrepancy may reflect differences in the laboratory methods in detection of cryoglobulin as well as patient selection bias considering a limited sample size.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…This nding was consistent with that of Italian study which reported type II cryoglobulins accounted for 88% in HBV related cryoglobulinemic vasculitis [5]. However, result in another previous Chines study suggested that type III cryoglobulinemia was more frequently seen in HBV related CryoGn [6]. This discrepancy may re ect differences in the laboratory methods in detection of cryoglobulin as well as patient selection bias considering a limited sample size.…”
Section: Treatment and Clinical Outcomessupporting
confidence: 90%
“…The majority of these patients (75%) presented after .10 years of HBV infection with predominantly type 3 cryoglobulinemia (polyclonal IgM -polyclonal IgG). This compares to a greater propensity (80%) of type 2 cryoglobulinemia (monoclonal IgM -polyclonal IgG) with type 1 MPGN in chronic HCV infection of .10-15 years (18). HBV patients with cryoglobulinemia may present with nephrotic syndrome, AKI, and systemic vasculitis with low C4 (92%) and low C3 (58%).…”
Section: Mpgnmentioning
confidence: 99%